2018
DOI: 10.1002/jbt.22266
|View full text |Cite
|
Sign up to set email alerts
|

High doses of sodium tungstate can promote mitochondrial dysfunction and oxidative stress in isolated mitochondria

Abstract: Tungstate (W) is recognized as an agent of environmental pollution and a substitute to depleted uranium. According to some preliminary studies, tungstate toxicity is related to the formation of reactive oxygen species (ROS) under abnormal pathological conditions. The kidneys and liver are the main tungstate accumulation sites and important targets of tungstate toxicity. Since the mitochondrion is the main ROS production site, we evaluated the mechanistic toxicity of tungstate in isolated mitochondria for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 29 publications
2
8
0
1
Order By: Relevance
“…The level of ROS was measured by flow cytometry and DCFH‐DA as reagent as described in the authors’ previous study (Cheraghi et al., 2019). In flow cytograms, nontreated isolated cells (control) showed relatively weak fluorescence signal because of self‐quenching.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The level of ROS was measured by flow cytometry and DCFH‐DA as reagent as described in the authors’ previous study (Cheraghi et al., 2019). In flow cytograms, nontreated isolated cells (control) showed relatively weak fluorescence signal because of self‐quenching.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced GSH level as a strong antioxidant system protected cells from damaging effects of ROS formation and oxidized GSH (Pourahmad et al., 2011). Lack of balance between oxidants and antioxidants levels led to oxidative damages in lipids, proteins and nucleic acids caused to initiation of cell death signaling (Cheraghi et al., 2019). Although ROS level increased after exposure to 3‐MCPD, no decrease in the GSH level was observed on different concentration of 3‐MCPD (except for 10 µM) in isolated kidney cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress causes damage to cell components, especially mitochondria, which are the site of ROS production and also the target of oxidative stress-induced damage [8]; previous reports have shown that ROS accumulation induced the mitochondrial respiratory chain damage [4]. Excessive uorine intake increases the accumulation of ROS in the liver, suggesting that uorine destroys the mitochondrial respiratory chain, which is mainly characterized by the occurrence of oxidative stress and the decrease of ATP content [33].…”
Section: Discussionmentioning
confidence: 99%
“…АФК выступают в роли стрессового фактора на энергетическом уровне клетки. Это приводит к снижению АТФ, что приводит к усиленному синтезу АТФ и снижению электрохимического градиента [18].…”
Section: обсуждение полученных результатовunclassified